Quantitative Analysis of Variable Extent of Anterior Clinoidectomy With Intradural and Extradural Approaches: 3-Dimensional Analysis and Cadaver Dissection. Issue 1 (March 2015) - Tripathi, Manjul; Chandra Deo, Rama; Damodaran, Natesan; Suri, Ashish; Srivastav, Vinkle; Baby, Britty; Singh, Ramandeep; Kumar, Subodh; Kalra, Prem; Banerjee, Subhashis; Prasad, Sanjiva; Paul, Kolin; et al.
Abstract : BACKGROUND: Drilling of the anterior clinoid process (ACP) is an integral component of surgical approaches for central and paracentral skull base lesions. The technique to drill ACP has evolved from pure intradural to extradural and combined techniques. OBJECTIVE: To describe the computerized morphometric evaluation of exposure of optic nerve and internal carotid artery with proposed tailored intradural (IDAC) and complete extradural (EDAC) anterior clinoidectomy. METHODS: We describe a morphometric subdivision of ACP into 4 quadrangles and 1 triangle on the basis of fixed bony landmarks. Computerized volumetric analysis with 3-dimensional laser scanning of dry-drilled bones for respective tailored IDAC and EDAC was performed. Both approaches were compared for the area and length of the optic nerve and internal carotid artery. Five cadaver heads were dissected on alternate sides with intradural and extradural techniques to evaluate exposure, surgical freedom, and angulation of approach. RESULTS: Complete anterior clinoidectomy provides a 2.5-times larger area and 2.7-times larger volume of ACP. Complete clinoidectomy deroofed the optic nerve to an equal extent as by proposed the partial tailored clinoidectomy approach. Tailored IDAC exposes only the distal dural ring, whereas complete EDAC exposes both the proximal and distal dural rings with complete exposure of the carotid cave. CONCLUSION: Quantitative comparative evaluation provides details of exposure and surgical ease with both techniques. We promote hybrid/EDAC technique for vascular pathologies because of better anatomic orientation. Extradural clinoidectomy is the preferred technique for midline cranial neoplasia. An awareness of different variations of clinoidectomy can prevent dependency on any particular approach and facilitate flexibility. ABBREVIATIONS: ACP, anterior clinoid process EDAC, extradural anterior clinoidectomy ICA, internal carotid artery IDAC, intradural anterior clinoidectomy MOB, meningo-orbital band ON, optic nerve SOF, superior orbital fissure Abstract : Supplemental Digital Content is Available in the Text.